THE ECONOMIC POTENTIAL OF COMMUNITY-BASED TOURISM MANAGEMENT IN EDUCATIONAL TOURISM AT SUBAK TEBA MAJELANGU - Ni Putu Yeni Ari Yastini; I Made Agus Mahaputra Atmaja; I Nengah Alit Nuriawan (Samā Jiva Jnānam (International Journal of Social Studies), 2024)
This study explores the economic potential and challenges of community-based tourism management in Subak Teba Majelangu, a rural area in Bali, Indonesia, known for its UNESCO-listed Subak irrigation system. The paper examines how integrating local wisdom, particularly the Balinese philosophy of Tri Hita Karana (harmony with nature, fellow humans, and spirituality), can guide sustainable tourism practices while fostering community empowerment. The Subak system, a complex agricultural water management method, is not only an important cultural asset but also a significant driver of eco-tourism, offering a unique opportunity to balance environmental conservation with economic development. This qualitative research combines a literature review, interviews with local stakeholders, and case study analysis. Findings suggest that community-based tourism in Subak Teba Majelangu holds considerable economic potential through direct revenue from eco-tourism activities, local handicrafts, and agricultural produce. The involvement of the community in tourism management ensures the equitable distribution of benefits, enhances cultural pride and supports sustainable practices. However, challenges such as inadequate infrastructure, limited capacity in tourism management, and external pressures from mass tourism threaten the long-term sustainability of the initiative. The study further explores how local wisdom embedded in the Tri Hita Karana philosophy supports the integration of sustainable tourism practices. It emphasizes the importance of maintaining harmony between tourism development, cultural preservation, and environmental protection. By fostering a shared vision for tourism management and investing in capacity-building, Subak Teba Majelangu can mitigate the negative impacts of tourism while maximizing its economic benefits. In conclusion, Subak Teba Majelangu presents a valuable model for sustainable, community-based tourism that can be replicated in other regions. Its success depends on continuous collaboration among local communities, government authorities, and external partners. The research highlights the critical need for strategic planning, infrastructure development, and education to ensure the preservation of both cultural heritage and natural resources while supporting local economic growth.